Media as a Form of Violence in the Context of Technological Determinism - AL, EYÜP (MARMARA UNIV, FAC COMMUNICATION, 2017)
The goal of the article is to prove that the media, as a form of violence, infiltrate every kind of content. The content is related to the centralization of the medium, which is the most important element that builds it. In this article, the media itself is regarded as the main source of violence because of its form/structure. As a method, this absolute effect of the medium gives rise to technological determinism. The question of what the medium are left behind is important and mediation-based mass media is the building block of violence in the context of technological determinism. It is here that technology-based means of communication puts the message/content in the way that it wants and becoming the reason of insignificant is a dominant element of symbolic violence. The imperative force on the content of the form/structure makes it necessary to think on the means of communication. Main goal of this article is to demonstrate that representation practices remain secondary and the main part is technological determinism. At this juncture, the article will prove that violence is the structural origin of the mass media medium in the context of technological determinism.
Keywords: Technological Determinism; Mass Media; Form/Structure; Content/Message; Symbolic Violence